SINTESIS KONTROL TSUKAMOTO-PID ADAPTIF PADA PENGERINGAN KUPANG - Dwi Hadidjaja; Akhmad Ahfas; Agus Hayatal Falah (Universitas Stikubank, 2026)
Traditional clam drying often suffers from energy inefficiency and inconsistent product quality due to manual temperature control that is unable to respond to dynamic environmental changes. This study proposes an adaptive hybrid control system integrating Fuzzy Tsukamoto and PID to enhance thermal stability and drying performance. Temperature and humidity were monitored in real time using a DHT22 sensor, while fuzzy inference and a self-tuning PID mechanism automatically adjusted control parameters. Performance was evaluated through error metrics, temperature stability, drying rate, and statistical validation. The system improved thermal efficiency to 85.2%, reduced Integral Absolute Error by 41.3%, decreased drying time by 22 minutes per cycle, and lowered overshoot by 87.3%. The optimal operating window occurred between 11:00–12:00 with a minimal error of 0.5 °C and a fuzzy output of 64.3, indicating a medium–fast drying rate. Temperature stability of ±0.8 °C results in a more uniform distribution of water content, texture and color, thereby increasing the selling value of the product. These findings demonstrate the strong potential of applying adaptive Tsukamoto–PID control to the seafood-based drying industry to improve process efficiency and quality consistency.